Controlled Synthesis of Different Submicron Crystalline Tellurium Structures by Adjusting Solution pH Value - Ding, Yi; Ren, Qifang; Chen, Shaohua (Asian Journal of Chemistry, 2012)
A new approach has been developed for the preparation of tellurium with various morphologies by a simple hydrothermal method using Na2TeO3 in ethylene glycol at 180 ºC. In this method, ethylene glycol acts not only as a surfactant but also as a reducing reagent, thus no additional reductants are needed. By control of the reaction conditions, especially, by adjusting of solution pH value, submicro brooms, submicro-channels and micro nanorods have been prepared.